The validity and reliability of motion analysis sensor system for wheelchair users (MASSWU) - Suansomchit, N.; Vorapojpisut, S.; Saadprai, S. (PLOS ONE, 2025)
The Motion Analysis Sensor System for Wheelchair Users (MASSWU) is designed to collect wheelchair movement data such as distance, duration, speed, and angular velocity during competitions and training sessions to enhance athlete performance. Developed as a simpler alternative to complex 2D motion analysis software, MASSWU was evaluated for validity, intra-rater and inter-rater reliability by comparison with the established 2D motion analysis program Kinovea. The assessment involved six wheelchair skill-related fitness tests performed under simulated real-world conditions by twenty-three healthy wheelchair users aged 18-35. The tests included One Stroke Push (distance), Muscle Power Sprint (speed), 10x5-meter Sprint (duration), Slalom (duration), and 360° Clockwise and 360° Anticlockwise Rotations (angular velocity). Validity was evaluated using the Pearson Correlation Coefficient, while intra-rater and inter-rater reliability were assessed through Intra-Class and Inter-Class Correlation Coefficients, respectively. MASSWU exhibited good to very good validity across all tests (r = 0.887-0.998). Both intra-rater reliability (ICC = 0.765-0.988) and inter-rater reliability (ICC = 0.899-0.996) ranged from good to very good. These results indicate that MASSWU is a highly valid and reliable tool compared with Kinovea for measuring wheelchair performance among these wheelchair skill-related fitness tests.